Optimization of heat treatment and calibration procedures for high temperature irradiation resistant thermocouples. Issue 4 (4th July 2018) - Skifton, Richard; Palmer, Joe; Calderoni, Pattrick
ABSTRACT: A detailed description is provided for the optimization of heat treatment and calibrating procedure for Idaho National Laboratory's high temperature irradiation resistant thermocouples (HTIR-TC). Also discussed is the implication of the procedures on the overall performance of the HTIR-TC finished product; in particular, for the case of long lead sections that are typical of sensors deployed in nuclear reactors. The effect on the measurement accuracy of fluctuations of the reference temperature and localized heating along the sensor lead is also investigated. A calibration graphical user interface (GUI) and accompanying script is presented for unifying the calibration process. A fifth-order polynomial function was found to be best for fitting HTIR-TC calibration data. The performance of the HTIR-TCs subject to the optimized heat treatment and calibration procedures is shown to be robust and consistent with other TC industry standards. Electromotive force curves versus length of the TC are presented to clarify positioning of TCs in general and how its effect on the calibrated temperatures.